Виявлення військових цілей за допомогою методів комп’ютерного зору - Любименко, Р. С. (ХНУРЕ, 2024)
This paper is devoted to the detection of military targets using computer vision methods. Two-stage and one-stage object detection algorithms are considered, along with a more detailed description of the most popular algorithms. The problems related to the detection of military objects are investigated, and possible solutions are proposed.
Keywords: виявлення військових цілей; методи комп’ютерного зору